Non-fiber Carbohydrates in Forages and Their Influence on Beef Production Systems - Villalba, Juan J.; Ates, Serkan; MacAdam, Jennifer W. (Frontiers in Sustainable Food Systems, 2021)
Forages can provide a complete diet for ruminant animals, increasing the sustainability of beef production systems worldwide while reducing competition with humans for agricultural land or grain crops. Much of the emphasis on the nutritional characteristics of forages has been on the fiber, sugars, starch, and protein they supply to the rumen, despite the fact that other less-explored constituents, i.e., neutral detergent soluble fiber (NDSF) and other non-structural or non-fiber carbohydrates (NFC) also play a key role in the nutrition of ruminants. This paper explores the less investigated potential of temperate legumes to accumulate levels of NFC comparable to corn silage or beet pulp in cool, dry environments under irrigation, and its implications for forage-based beef production systems. We conclude that genetic or managerial interventions (i.e., breeding programs, defoliation frequency) or ecological conditions (i.e., climate, elevation) that increase concentrations of NFC in legumes can enhance beef production, meat quality, and the efficiency of nitrogen utilization by ruminants while reducing environmental impacts.